GOLDEN QUADRILATERAL OF THE MAXILLARY BONE - Alexandru Misăiloaie; Norina Forna; Cristian Constantin Budacu; Olgun Chemal; Denisa- Mihaela Misăiloaie; Anca Sava (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study The purpose of this study is to demonstrate the effectiveness of two primary stability measurement tools: insertion torque value and the stability coefficient using resonance frequency analysis with the ISQ (Implant Stability Quotient) in the therapeutic decision for the immediate loading of dental implants anchored in the golden quadrilateral of the maxillary bone. Material and methods 22 patients presenting with total edentation or advanced periodontal disease were consulted and operated in a private oral surgery clinic. A total of 110 conical- shaped implants were inserted. Results The average ISQ scale value for implant 1.1 was higher in the control group but it did not reach statistical significance between the two statistically analyzed groups. The average ISQ scale value for implant 1.4 was higher in the test group, compared to the control group, showing statistically significant significance. Patients in the control group associated a higher average value for the ISQ scale in the case of implant 2.4 , being a statistically significant parameter in our study group. The average insertion torque value for the implant was higher in the test group of patients at implant 1.1, implant 1.4 and implant 2.4 . Conclusions The insertion torque, along with the resonance frequency analysis, serve as tools for measuring primary stability. In our study, both groups exhibited adequate primary stability for immediate prosthetic loading, but the distal implants anchored in the golden quadrilateral of the maxilla showed a significant value.